PENERAPAN MODEL PEMBELAJARAN PENEMUAN TERBIMBING (GUIDED DISCOVERY) UNTUK MENINGKATKAN HASIL BELAJAR SISWA PADA POKOK BAHASAN KOLOID DI KELAS XI IPA SMA NEGERI 5 PEKANBARU - Aprilia, Winda Rezki; Copriady, Jimmi; Haryati, Sri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The research about application of guided discovery learning model aims to improve students learning outcomes on the subject of colloid in class XI Science at SMAN 5 Pekanbaru. Guided discovery learning model is a model the theacer gave the students examples of spesific topics and guide the students to understand the subjects. The type of research is experiment research with design randomized control group pretest-posttest. The sample consisted of two classes, XI Science 6 as experiment class and XI Science 5 as control class that randomly selected after testing normality and homogeneity. Experiment class is the class that implemented guided discovery learning model while the untraeted control class. Data analysis techniques used is the t-test. Results of the analysis it was found that tscore > ttable (1,89 > 1,67), it means that the application guided discovery learning model can improve students outcomes on the subject of colloid in class XI Science SMAN 5 Pekanbaru. The category improvement of students learning outcomes including high category with N-gain = 0,84.Key words : Guided Discovery Learning Model, Learning Outcomes, Colloid.